Transforming Western Democracy In Southeast Asia: The Case Of Lanao Del Sur, The Philippines - Kim, Dong Yeob (Penerbit Universiti Sains Malaysia (USM Press), 2018)
The question “why transplanted Western democracy in Southeast Asia could not thrive as intended” has yet to be answered. A possible answer to the question could be found in the dynamics of cultural encounter between the traditional Southeast Asian society and Western democracy. The case of the Muslim province of Lanao del Sur in the Philippines provides us an understanding how Western democratic institutions were translated and localised. The adaptation of Western democracy meant to restructure the political boundaries and especially for the Muslim Maranao to integrate into the bigger Christian dominated polity. Although the system of authority changed from the traditional to the so-called legal one, the traditional conception of social relations and authority still shape the Maranao politics. Western democratic institutions are observed only superfcially. And the transformed Western democracy caused conﬂicts and armed struggle among the locals.